Kompetensi Profesional Sebagai Penentu Efektivitas Kerja Dosen: Studi Empiris Di Politeknik Pariwisata Palembang - Firmansyah, Firmansyah; Suandi, Suandi; Fanada, Mery; juliartha, Edwar; Gustiawan, Randa (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2026)
The quality of vocational higher education is strongly determined by how effectively its lecturers perform. Among various influencing factors, professional competence is frequently cited as a fundamental prerequisite, yet empirical evidence from Indonesian vocational tourism higher education institutions remains scarce. This article examines the effect of professional competence on lecturer work effectiveness at the Palembang Tourism Polytechnic. A quantitative correlational-regression design was employed. The population and sample comprised all 58 active lecturers (total sampling). Data were collected using a validated Likert-scale questionnaire (12 valid items; ?=0.789) and analyzed via simple linear regression. Results indicate that professional competence positively and significantly influences lecturer work effectiveness, with the regression equation ? = 27.096 + 0.709X, t-value of 4.483 (p<0.01), and a coefficient of determination R²=0.265 (26.5% contribution). This finding suggests that nearly one-third of the variation in lecturer work effectiveness can be explained solely by professional competence. Practical implications include the need for structured, needs-based competency development programs, particularly in the dimensions of scientific research and continuous professional development.